Heat monitor 2023: Despite continued price increases, lower decline in households' heating energy consumption - Sophie M. Behr; Till Köveker; Merve Kücük (DIW Weekly Report, 2024)
In 2023, heating energy prices increased by substantial 31 percent compared to the previous year, following a 33 percent increase already seen in 2022. Calculations based on data from the energy service provider ista show average price increases were the highest in the German state of Rhineland- Palatinate, and the lowest in Hamburg. Owing to these price hikes and ongoing energy-saving efforts, the temperature- adjusted heating energy consumption of two- and multi- apartment buildings in Germany covered in this study fell by an average of four percent compared to the previous year, which was slightly less than the decline observed in 2022. The biggest energy savings were seen in households in Saxony. At the same time, temperature-adjusted CO2 emissions per square meter also fell, although to a slightly lesser extent than in 2022. With heating energy prices stabilizing, the momentum in emissions reductions is expected to slow down. If Germany is to meet its climate targets, further efforts are needed, particularly in improving energy efficiency in the building sector and in switching to renewable heating systems.
Keywords: R31; Q21; Q40; 330; Heating demand; heating costs; building energy efficiency; residential buildings; gas prices